Możliwości finansowania rozwoju kadr przedsiębiorstw z Europejskiego Funduszu Społecznego. Założenia i realizacja - Kwiatkowska-Ciotucha, Dorota (Possibilities of Firms' Staff Development Financing from the European Social Fund, 2007)
The paper presents possibilities of firms' staff development financing from the European Social Fund in Poland during the period of 2004-2006. Problems are presented from theoretical point of view (based on official documents) as well as from practical aspects (based on practical procedures used on [application and realization phases).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 221-229